Volcanic‐Tectonic Structure of the Mount Dent Oceanic Core Complex in the Ultraslow Mid‐Cayman Spreading Center Determined From Detailed Seafloor Investigation. (7th March 2019) - Haughton, G. A.; Hayman, N. W.; Searle, R. C.; Le Bas, T.; Murton, B. J.
Abstract: The flanks of the ultraslow‐spreading Mid‐Cayman Spreading Center (MCSC) are characterized by domal massifs or oceanic core complexes (OCCs). The most prominent of these, Mount Dent, comprises lower‐crustal and upper‐mantle lithologies and hosts the Von Damm vent field 12 km west of the axial deep. Here, presented autonomous underwater vehicle‐derived swath sonar (multibeam) mapping and deep‐towed side‐scan sonar imagery lead to our interpretation that: (i) slip along the OCC‐bounding detachment fault is ceasing, (ii) the termination zone, where detachment fault meets the hanging wall, is disintegrating, (iii) the domed surface of the OCC is cut by steep north‐south extensional faulting, and (iv) the breakaway zone is cut by outward facing faults. The Von Damm vent field and dispersed pockmarks on the OCC's south flank further suggest that hydrothermal fluid flow is pervasive within the faulted OCC. On the axial floor of the MCSC, bright acoustic backscatter and multibeam bathymetry reveal: (v) a volcanic detachment hanging wall, (vi) a major fault rifting the southern flank of Mount Dent, and (vii) a young axial volcanic ridge intersecting its northern flank. These observations are described by a conceptual model wherein detachment faulting and OCC exhumation are ceasing during an increase in magmatic intrusion, brittle deformation, and hydrothermal circulation within the OCC. Together, this high‐resolution view of the MCSC provides an instructive example of how OCCs, formed within an overall melt‐starved ultraslow spreading center, can undergo magmatism, hydrothermal activity, and faulting in much the same way as expected in magmatically more robust slow‐spreading centers elsewhere. Plain Language Summary: Mid‐ocean ridges create the seafloor of the ocean basins, and the processes involved range from the eruption of volcanoes to the generation of submarine hydrothermal vents. A small spreading center in the Caribbean Sea—the Mid‐Cayman Spreading Center—spreads at such a slow rate that instead of a steady eruption of volcanic material, tectonic faults pull the deeper parts of the Earth to the surface forming Mount Everest‐scale mountains. In 2010 and 2013 we collected data from the most prominent massif in the Cayman Trough using cutting‐edge mapping tools such as an autonomous underwater vehicle, or AUV. Our data show that the massif is complex internally, breaking up by tectonic forces, intruded by magma, and eroded at the surface. All of these processes are related to the flow of fluids through the crust that sustain the Von Damm vent field, a globally distinct vent field in terms of its biology and chemistry. Mount Dent is likely similar to many other such complexes around the world, including other deep, slow‐spreading centers. Key Points: The Mid‐Cayman Spreading Center is an example of how magmatism can drive cycles of ocean core complex development even at ultraslow rates Decreasing detachment fault slip is marked by crosscutting higher angle faults and patterns of mass wasting and sedimentation The surface expression of hydrothermal fluid flow in vents and pockmarks is linked with the mechanical evolution of oceanic core complexes